Use Of Oil Palm Empty Fruit Bunch For Lignophenol Production - Syed Abdullah, Sharifah Soplah (2008)

(untitled)
Oil palm empty fruit bunch (OPEFB) is a by-product in palm oil industry and represents an abundant, inexpensive and renewable resource which has not been utilized satisfactorily. It can be categorized as lignocellulosic material due to its cellulose, hemicellulose and lignin content. Due to the reasons, this research was done to evaluate the potential of OPEFB as starting material for lignophenol production by using one step and two-step processes to compare the efficiency of the methods. The best method was further applied for the next experiment to produce lignophenols from different type of OPEFB. The separation of lignin from OPEFB is based on the phase separation reaction system at room temperature (~ 28°C) to produce lignophenol. This process composed of phenol derivative (p-cresol) and concentrated acid (72% sulfuric acid) where lignin is present in organic phase and carbohydrates in aqueous phase after 1 hour of stirring. From the results obtained, the two step process is the best method to produce lignophenol due to competitive yield obtained and less chemicals used compared to one step process. The yield of lignophenol produced by one step and two step processes were 68% and 61%, respectively. Three types of OPEFB have been used, i.e. extractives free OPEFB (LP1), non-extractives free OPEFB (LP2) and OPEFB powder obtained from Sabutek Mill, Perak (LP3). The chemical composition of each OPEFB was determined prior to production of lignophenol by two step process. Basically, the lignin content in LP1 and LP2 were not so much different as compared to LP3 which has lower lignin and cellulose content. There were no difference in yield of lignophenol being produced from LP1 and LP2 which gave 61±1% respectively, whereas LP3 gave 56±1% yield based on lignin content. Lignophenol from LP1 and LP2 also appeared in white pinkish color which is comparable to the previous work. However, lignophenol from LP3 appeared in dark brown color. The sugars hydrolyzed in the phase separation system in terms of percent conversion were 89%, 99% and 97% in LP1, LP2 and LP3, respectively. The lignophenol sample from LP1, LP2 and LP3 were further analyzed and characterized by Proton Nuclear Magnetic Resonance (1H-NMR), Fourier Transform Infrared Spectroscopy (FTIR), Gel Permeation Chromatography (GPC), Ultraviolet spectroscopy (UV) and thermomechanical analysis (TMA). However, LP3 could not be analyzed due to insolubility in the solvents used. From the results obtained, lignophenol from LP1 and LP2 showed similar results in structure and physical properties. The molecular weight of lignophenols from LP1 and LP2 were 5759 g mol-1 and 5866 g mol-1, respectively. There were no significant difference in the amount of attached cresol between LP1 and LP2 which gave 26±1%. In summary, it can be concluded that OPEFB has a good potential as a starting material in lignophenol production by using two step process. Furthermore, it does not require ethanol/benzene extraction to treat the material.